Use Of Web Services For The Localization Of Rolling Stock With Utilization Technology Oracle Spatial - Fikejz, Jan; Merta, Jan; Oborník, Jakub (University of Genoa, 2016)
This article deals with utilization of web services for the localization of rolling stock on the railway network using Oracle Spatial technology. Attention is focused on the description of the rolling stock location in a designed model of the Czech Republic railway network. Further attention is aimed on the design of web services for localization of rolling stock position on the server side with additional information for passengers.
Použití webových služeb pro lokalizaci kolejových vozidel s využitím technologie Oracle Spatial
Keywords: Use; Web; Services; For; The; Localization; Rolling; Stock; With; Utilization; Technology; Oracle; Spatial; Použití; webových; služeb; pro; lokalizaci; kolejových; vozidel; využitím; technologie; Oracle; Spatial